Improving Early Childhood Literacy Abilities Through Digital 3d With Augmented Reality Technology - Sari Rizki; Rahma Rahma; Basri, Novysa (Universitas Negeri Semarang, 2024)
This research aims to discuss the results of developing 3D digital teaching media with augmented reality for children's literacy. Children can access AR Teaching Media independently. The method in this study uses a four-D design, namely define designed to analyze teachers' abilities in the context of Teaching Media to what extent teachers understand digital-based Teaching Media. Design is designing digital-based learning media software, namely 3D Teaching Media with AR technology, researchers will construct literacy materials in digital Teaching Media designs that are in accordance with literacy materials for early childhood. Develop is a stage that includes expert validation tests and feasibility of the initial design of Teaching Media and is then developed according to the direction of expert validation tests and feasibility tests. Dissemination is a stage to disseminate and implement Teaching Media products. The results of this study are the development of digital 3D-based teaching media with AR technology has been proven effective in improving early childhood literacy skills. The use of AR technology not only improves literacy skills, but also children's motivation and involvement in the learning process. With wider adoption and support for technology access and training for educators, AR-based teaching media can be a very useful tool for developing literacy in early childhood.